Extending the Multimode Resource-Constrained Project Scheduling Problem by Including Value Considerations - Balouka, Noemie; Cohen, Izak; Shtub, Avraham (IEEE transactions on engineering management, 2016)
The current trend in modern project management methodologies is to maximize project values. We suggest a quantitative model that balances time, cost, and value. It generates detailed project plans, which are feasible with respect to time, cost, and resource-constraints, and considers interactions between technical performance, time, and cost. Such interactions, which existing project management models typically ignore or project managers deal with intuitively, are important for increasing projects' values. The model, which extends the multimode resource-constrained project scheduling problem by including value, generates an efficient frontier that includes the best project plans for varying project costs. We provide illustrative examples to demonstrate the suggested approach.